Evaluating Cryptosporidium oocyst removal in SSF: impact of underwater skimming and dry skimming - Bretagne, Sophie L.; Chipps, Michael; Doggett, Ian; Bradwell, Michael C. J.; Hardiman, Heide; Harris, Jim A.; Hassard, Francis (Elsevier, 2026)
Cryptosporidium is a protozoan parasite that presents significant challenges to water supply security due to its resilience against conventional chemical disinfection. This study evaluates the effectiveness of two slow sand filter (SSF) skimming techniques-dry skimming (DS) and underwater skimming (UWS), in removing Cryptosporidium oocysts under pilot-scale conditions using 10 filters. Oocyst retention was monitored during dosing, post-dosing, and following the skimming event. Results demonstrated that UWS achieved superior pathogen removal, evidenced by fewer oocyst breakthroughs and higher cumulative log retention values (cLRtVs). During dosing, UWS filters attained cLRtVs consistently exceeding 6.6, whereas DS filters averaged 5.6. In the post-dosing period, UWS retained cLRtVs above 6.9, while DS averaged 5.9. A quantitative microbial risk assessment (QMRA) indicated a substantially lower probability of illness from oocyst breakthrough in UWS-treated water, with a daily risk of ∼2.6 × 10^-6 for immunocompetent individuals, compared to up to 8.2 × 10^-6 in DS-treated water, equating to a 3.2-fold risk reduction. These findings highlight that the UWS maintenance technique enhances SSF operation by improving pathogen retention while enabling minimal filter downtime, thereby contributing to improved water safety and public health protection. The work also provides novel empirical data and theoretical predictions regarding the potential risk of Cryptosporidium penetration or compromised water quality arising from the routine requirement to skim SSFs.
Keywords: 30 Agricultural, Veterinary and Food Sciences; 40 Engineering; 4011 Environmental Engineering; Digestive Diseases; 2.2 Factors relating to the physical environment; Infection; Environmental Sciences; Cryptosporidium; Slow sand filtration; Underwater skimming; Quantitative microbial risk assessment; Public health protection; Dry Skimming